CIM control design using grafcet - Rusin, Siti Ruzaimah (2005)
This project is concerned with learning and exploring industrial automation technologies, such as control systems, Computer Integrated Manufacturing system and the relationship between these major components. The CIM70A System will be used in this project and located at Automation Lab, Kuithho. The project is divided into two major parts. In the first part, the author familiarized herself with the operation and all the functions of the related industrial components ofthe CIM70A System, such as the sensors, actuators, and the valves. In the second part, the author aimed to study GRAFCET and attempts to relate between the graphical representation and mathematical model using PLC programs. With this formal approach, the programming will be written more neatly, well arranged and standardized. This project successfully explores the possibility of designing the control program using GRAFCET.